Motivational Climate Sport Youth Scale: Measurement invariance across gender and five different sports - Monteiro, Diogo (2018)
The aim of this study was to analyze the psychometric properties of the Portuguese version of the Motivational Climate Sport Youth Scale (MCSYSp) and invariance across gender and different sports (swimming, soccer, handball, basketball, futsal). A total of 4,569 athletes (3,053 males, 1,516 females) from soccer (1,098), swimming (1,049), basketball (1,754), futsal (340), and handball (328) participated in this study, with ages between 10 and 20 years (M = 15.13; SD = 1.95). The results show that the original model (two factors/12 items) did not adjust to the data in a satisfactory way; therefore, it was necessary to change the model by removing four items (two from each factor). Subsequently, the model adjusted to the data in a satisfactory way (χ² = 499.84; df = 19; χ²/df = 26.30; p < .001; SRMR = .037; TLI = .923; CFI = .948; RMSEA = .074; IC90% .069–.080) and was invariant by gender and team sports (soccer, handball, basketball, futsal) (∆CFI≤.01); however, it was not invariant between swimming and team sports (soccer, handball, basketball, futsal) (∆CFI ≥ .01). In conclusion, the MCSYSp (two factors/eight items) is a valid and reliable choice that is transversal not only to gender, but also to the different studied team sports to measure the perception of the motivational climate in athletes. Future studies can research more deeply the invariance analysis between individual sports to better understand the invariance of the model between individual and team sports.